Changing fertility and heterogeneous motherhood effects: Revisiting the effects of a parental benefits reform - Bernd Fitzenberger; Arnim Seidlitz (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Using a semiparametric event study approach with a control group, we estimate the effect of motherhood on labor market outcomes in Germany, the child penalty. We further investigate how the 2007 parental benefits reform changed the child penalty while accounting for fertility effects. A large novel data set linking data from two administrative sources provides information on all births. Our estimation approach accounts for motherhood being a staggered treatment. The reform has small positive medium-run effects employment outcomes. It changes the selection into motherhood and has certain heterogeneous effects. However, the reform did little to reduce the average child penalty. – – Mit einem semiparametrischen "Event-Study-Ansatz" unter Verwendung einer Kontrollgruppe schätzen wir den Effekt der Geburt des ersten Kindes auf Verdienste und Erwerbsbeteiligung der Mütter, die sogenannte "child penalty". Wir behandeln Mutterschaft als ein "zeitlich gestaffeltes Treatment". Außerdem untersuchen wir den Effekt des 2007 eingeführten Elterngeldes auf die "child penalty" - unter Berücksichtigung der Fertilitätseffekte. Ein großer neuer Datensatz, der Daten aus zwei administrativen Quellen miteinander verknüpft, enthält Informationen über alle Geburten. Die Reform hat geringe positive mittelfristige Auswirkungen auf den Beschäftigungsverlauf. Sie verändert die Selektion in die Fertilität und es zeigen sich gruppenspezifische Effektunterschiede. Jedoch hat die Reform die durchschnittliche "child penalty" kaum verringert.
Keywords: J08; J13; J16; J22; 330; Child penalty; parental benefit reform; semiparametric event study approach